Evaluasi Stabilitas Proses Produksi Keramik Berbasis Statistical Process Control - Dharmawanto, Doni Ferdio Iqbal; Jumali, Muhamad (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Process variation in ceramic manufacturing significantly contributes to product defects and inconsistent quality performance. This study evaluates the statistical stability of a ceramic production line using an attribute-based Statistical Process Control approach. A total of 36,000 units were inspected during January 2026 with a constant sample size of 100 units every two hours, resulting in 360 subgroups. An np control chart was employed to assess process stability, followed by Pareto analysis to determine dominant defect categories and structured root cause mapping to identify potential sources of variation. The average defect proportion was 4.2%, with seven subgroups exceeding the upper control limit, indicating the presence of special-cause variation. Crack and crawling defects accounted for 74.8% of total nonconformities and were primarily associated with drying and glazing stages. The findings indicate that the process was not fully under statistical control and requires targeted corrective actions to improve process consistency.